Examining the Impact of Risk Tolerance and Risk Aversion on the Individual Financial Performance in the Kingdom of Bahrain - Ogalo, Habil Slade (Asian Journal of Empirical Research, 2019)
With growing tougher economic conditions, everyone is struggling to safeguard their financial assets and invest them carefully. However, there are certain unavoidable risk factors that every person should be aware of since they have a potential to influence individual`s financial stability. With this notion, the present study attempted to investigate how individual financial performance can be managed and enhanced. Therein, the study attempted to examine the role of risk tolerance and risk aversion factors in an individual towards its financial performance. Through sampling 450 white collar working professionals from retail and financial sectors in the kingdom of Bahrain, the present study found a significant positive relationship between risk tolerance and individual financial performance. Accordingly, the study also reported a significant positive relationship between risk aversion and financial performance. The study has contributed towards a very important topic particularly in an emerging economy like Bahrain. The study forwards implications for practice and scope for future studies based on the findings.